Reimagining Islamic Scholarship: Integrating Psychology, Gender, and Public Policy - Nadirah, Sitti (Sinergi International Journal of Islamic Studies, 2023)
This narrative review explores the significance and application of interdisciplinary approaches in Islamic studies across domains such as psychology, gender, law, education, and public policy. The study aims to understand how integrating diverse academic disciplines enhances the theoretical depth and practical relevance of Islamic scholarship in addressing contemporary societal challenges. Using a systematic literature search strategy across databases like Scopus and Google Scholar, the review includes peer-reviewed empirical and theoretical studies that utilize interdisciplinary frameworks. The findings reveal that interdisciplinary strategies offer enriched insights into issues such as spiritual well-being, ethical leadership, gender justice, and culturally grounded policy-making. For instance, integrating psychology with Islamic teachings provides new models for understanding mental health and moral education, while feminist legal theory helps reframe gender roles in Islamic jurisprudence. The review also uncovers successful models of interdisciplinary practice in Southeast Asia and globally, including the integration of fiqh with astronomy and religiously-informed environmental conservation. However, systemic barriers such as academic bureaucracy, mono-disciplinary dominance, and resource constraints remain significant challenges. Addressing these requires institutional reform, increased funding, and enhanced collaboration across academic and community stakeholders. The study concludes by recommending more inclusive, locally adapted, and empirically grounded research to expand the impact of interdisciplinary Islamic studies. These approaches are essential in making Islamic scholarship more responsive, socially engaged, and transformative.